2009
DOI: 10.2164/jandrol.108.006395
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Egg Yolk on Cryopreservation of Rhesus Monkey Ejaculated and Epididymal Sperm

Abstract: Sperm cryopreservation in rhesus monkeys has not been successful when applied in standard, intravaginal artificial insemination; thus, there is a need for substantial improvement in current cryopreservation protocols. The present study was part of our systematic approach to optimize the cryopreservation procedure. Specifically, we tested whether modification of the concentration of egg yolk, the dilution method, and the time delay between ejaculation and adding egg yolk would result in significant improvement … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
8
0

Year Published

2009
2009
2019
2019

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 50 publications
2
8
0
Order By: Relevance
“…However, similar to results achieved with ram [26] and rhesus monkey [27] spermatozoa, the post-thaw motility of sperm samples did not decrease when the EY concentration was lowered. This detrimental effect on SV could be related to either the largest proportion of lactose in the extender or the poor cryoprotective ability of the lowered EY concentration with respect to the lactose proportion.…”
Section: Discussionsupporting
confidence: 82%
“…However, similar to results achieved with ram [26] and rhesus monkey [27] spermatozoa, the post-thaw motility of sperm samples did not decrease when the EY concentration was lowered. This detrimental effect on SV could be related to either the largest proportion of lactose in the extender or the poor cryoprotective ability of the lowered EY concentration with respect to the lactose proportion.…”
Section: Discussionsupporting
confidence: 82%
“…Though the exact means by which egg yolk helps sperm survive the cryopreservation process is unknown, it has generally been assumed that egg yolk stabilizes the sperm plasma membrane either directly, by forming a protective film [22] or replacing lost phospholipids [11,12,30], or indirectly by reducing the deleterious effect of seminal plasma proteins on the sperm membrane [2]. Yet, in the rhesus, a direct association of egg yolk with the sperm membrane seems to be the more likely explanation as egg yolk has been found to be equally necessary for protecting epididymal sperm as it is for ejaculated sperm [7]. …”
Section: Discussionmentioning
confidence: 99%
“…Our results indicated that reducing the concentration of EY from 20 to 10% in a lactose-based diluent was detrimental for SV after thawing in all the sperm samples, even those treated with CLC prior freezing. However, and similarly to results achieved with ram (Marco-Jiménez et al, 2004) and rhesus monkey (Dong and Vandevoort, 2009) spermatozoa, the post-thaw motility of sperm samples did not decrease when the EY concentration was lowered. This detrimental effect in SV could be related to either the largest proportion of lactose in the extender or the poor cryoprotective ability of the lowered EY concentration with respect to the lactose proportion.…”
Section: Discussionsupporting
confidence: 81%